Incidence of potentially human papillomavirus–related neoplasms in the United States, 1978 to 2007. Issue 12 (11th April 2013) - Kurdgelashvili, George; Dores, Graça M.; Srour, Samer A.; Chaturvedi, Anil K.; Huycke, Mark M.; Devesa, Susan S.
Abstract : BACKGROUND: Population‐based studies comprehensively describing incidence patterns of human papillomavirus (HPV)‐related preinvasive and invasive neoplasms prior to widespread HPV vaccination are sparse. METHODS: Age‐adjusted incidence rates (IRs), IR ratios (IRRs), and annual percent changes (APCs) in IRs were calculated for potentially HPV‐related tumors diagnosed in the Surveillance, Epidemiology and End Results (SEER) Program during 1978 through 2007. RESULTS: Overall IRs for preinvasive tumors were significantly higher than for invasive squamous cell tumors of cervix (IRR = 3.42), vulva (IRR = 1.87), and vagina (IRR = 1.19) and significantly lower for adenomatous cervical tumors (IRR = 0.43), and squamous cell tumors of penis (IRR = 0.64), anus (males, IRR = 0.53; females, IRR = 0.14), and head and neck (H&N) (males, IRR = 0.01; females, IRR = 0.02). Incidence of preinvasive squamous tumors of cervix, vagina, and penis rose rapidly over time and decreased for invasive neoplasms. The most rapid increases occurred for preinvasive (males, APC = 16.0; females, APC = 7.3) and invasive anal tumors (males, APC = 3.6; females, APC = 2.3). IR patterns were generally similar among evaluable racial/ethnic groups, with the exception of H&N invasive tumor IRs which increased exclusively among white males. CONCLUSIONS: Contrary to the opposing trends of preinvasive and invasive squamous tumors of cervix, vagina, and penis, preinvasive and invasive anal tumor IRs increased significantly over time by sex, age, and racial/ethnic groups. Successful HPV vaccination programs are needed to measurably reduce incidence of HPV‐related neoplasms in the future, particularly for cancer sites with rising incidence rates for which effective screening modalities are limited. Cancer 2013;119:2291–2299. © 2013 American Cancer Society. Abstract : To assess incidence patterns and trends in the era before human papillomavirus (HPV) vaccination, the authors describe the incidence of preinvasive and invasive potentially HPV‐related neoplasms in the US population during 1978 to 2007. Notable findings include the rising incidence of HPV‐related head and neck cancers among white males and the exponential increase in incidence of preinvasive and invasive anal tumors by sex, age, and racial/ethnic groups, supporting an urgent need for vaccination given the absence of effective screening modalities for tumors at these sites.